A blended mobile learning experience: the Nomadis case. (9th October 2008) - Diamantini, Davide; Pieri, Michelle
This paper focuses on a blended mobile learning experience produced by the Nomadis Laboratory of the University of Milan-Bicocca. This experience has included two face-to-face meetings and a didactic unit that is accessible through PocketPC. This experience has included three steps: Step 1, face-to-face meeting with the participants, where the PocketPC was introduced and distributed to them after the presentation of a prequestionnaire; Step 2, the supply of the didactic unit; Step 3, a face-to-face meeting with the participants for them to share their comments and the distribution of a questionnaire to assess the experience that was made.